Identification and validation of G protein-coupled receptors modulating flow-dependent signaling pathways in vascular endothelial cells - Qiu, Dike; Xu, Ke; Chung, Namjin; Robbins, Jennifer; Luo, Robert; Lawrence, Michael; He, Aiqing; Yu, Fei; Alt, Andrew; Miller, Michael M.; Hangeland, Jon; Feder, John N.; et al. (Frontiers in Molecular Biosciences, 2023)
Vascular endothelial cells are exposed to mechanical forces due to their presence at the interface between the vessel wall and flowing blood. The patterns of these mechanical forces (laminar vs. turbulent) regulate endothelial cell function and play an important role in determining endothelial phenotype and ultimately cardiovascular health. One of the key transcriptional mediators of the positive effects of laminar flow patterns on endothelial cell phenotype is the zinc-finger transcription factor, krüppel-like factor 2 (KLF2). Given its importance in maintaining a healthy endothelium, we sought to identify endothelial regulators of the KLF2 transcriptional program as potential new therapeutic approaches to treating cardiovascular disease. Using an approach that utilized both bioinformatics and targeted gene knockdown, we identified endothelial GPCRs capable of modulating KLF2 expression. Genetic screening using siRNAs directed to these GPCRs identified 12 potential GPCR targets that could modulate the KLF2 program, including a subset capable of regulating flow- induced KLF2 expression in primary endothelial cells. Among these targets, we describe the ability of several GPCRs (GPR116, SSTR3, GPR101, LGR4) to affect KLF2 transcriptional activation. We also identify these targets as potential validated targets for the development of novel treatments targeting the endothelium. Finally, we highlight the initiation of drug discovery efforts for LGR4 and report the identification of the first known synthetic ligands to this receptor as a proof-of-concept for pathway-directed phenotypic screening to identify novel drug targets.